Artificial Intelligence (AI) and the Educational Process: Using AI to Enhance Student Performance in Content Skills - Aljohani, Nouf (My University, 2019)
This paper examines the effectiveness of using audio artificial intelligence in Saudi classrooms. Currently, high school students in Saudi Arabia find physics difficult and they struggle to remain motivated to learn. By facilitating students’ interaction with the activities that use Google Home Mini, it is anticipated that the degree of student achievement in physics can be increased. One participating class of students will be divided into two groups, the experimental group and the control group. The experimental group will engage with AI technology through Google Home Mini, under the supervision of the teacher. The control group will receive only traditional instruction from the teacher. The study will take place over a full semester. Student performance will be evaluated by using pre- and post- curriculum-based assessments of each group. The researcher then will compare the results using statistical tests via the SPSS program. The effectiveness of Google Home Mini will be measured using the Blake equation to determine the average gain (Blake, Sutton, Masson, & Phillips, 1986). The target indicator of success for the experimental group is a score of 90% on the post-assessment. AI is important in education because of its inherent strength in helping to address students’ learning needs in the classroom. AI systems provide flexibility in presenting scientific material and in responding to students’ interests and needs. AI systems benefit students through their ability to support information gathering and processing that enables greater diversity of response. There are many competing types of intelligence, including the capacity for logic, understanding, planning, emotional knowledge, self-awareness, creativity, problem solving, and learning. However, Tegmark (2018) asserts that intelligence is defined as “the ability to accomplish complex goals” (pp. 4-5). It is anticipated that using Google Home Mini in the classroom will support learners to develop this kind of intelligence and achieve the content-area goals.
Keywords: Artificial Intelligence (AI); Deep learning; Google Home mini; Alexa; Content Skills; Individual Learning; Experiential Learning